Heat Pump Drying of Fruits and Vegetables: Principles and Potentials for Sub-Saharan Africa - Folasayo Fayose; Zhongjie Huan (International Journal of Food Science)
Heat pump technology has been used for heating, ventilation, and air-conditioning in domestic and industrial sectors in most developed countries of the world including South Africa. However, heat pump drying (HPD) of fruits and vegetables has been largely unexploited in South Africa and by extension to the sub-Saharan African region. Although studies on heat pump drying started in South Africa several years ago, not much progress has been recorded to date. Many potential users view heat pump drying technology as fragile, slow, and high capital intensive when compared with conventional dryer. This paper tried to divulge the principles and potentials of heat pump drying technology and the conditions for its optimum use. Also, various methods of quantifying performances during heat pump drying as well as the quality of the dried products are highlighted. Necessary factors for maximizing the capacity and efficiency of a heat pump dryer were identified. Finally, the erroneous view that heat pump drying is not feasible economically in sub-Saharan Africa was clarified.